Spiritual Leadership : a Biblical Theology of the Role of the Spirit in the Leadership of God's People - Huffstutler, David (Wipf and Stock Publishers, 2016)
How should we see the Spirit at work in spiritual leaders today? How did the Spirit work through spiritual leaders in the Bible? While many books on spiritual leadership look at the culture around us and offer sound advice from biblical principles, this study asks Scripture first what the Spirit did through spiritual leaders in the Bible in order to figure out what the Spirit should be doing through spiritual leaders today.